Biosorption of Fluoride from Aqueous Solutions Using Bacillus subtilis Biomass - Krishna, K.S.L. Ramya; Yamuna, G.; Divya, P.; Muddada, Sudhamani (Asian Journal of Chemistry, 2017)
Biosorption of fluoride from aqueous solutions by using Bacillus subtilis was characterized. The effect of initial concentration of fluoride ion on the adsorption process was investigated. The experimental data for removal of fluoride showed the better fit with the Langmuir isotherm than with the Freundlich or Temkin isotherms. An initial fluoride concentration of 100 mg/L was found to be optimal for adsorption efficiency. Scanning electron microscopy and energy dispersive X-ray spectrometry (SEM-EDX) analysis proved that the fluoride was biosorbed onto the biomass. Fourier transform infrared (FTIR) spectra indicated the involvement of various functional groups in the adsorption process.